2019
DOI: 10.1038/s41418-018-0271-8
|View full text |Cite
|
Sign up to set email alerts
|

TAK1 regulates endothelial cell necroptosis and tumor metastasis

Abstract: Formation of metastases is the major cause of death in patients diagnosed with cancer. It is a complex multistep process, including tumor cell migration, intravasation, survival in the circulation, and extravasation. Previously it was shown that tumor cell-induced endothelial necroptosis promotes tumor cell extravasation and metastasis. Here, we identified endothelial TGF-β-activated kinase 1 (TAK1) as a critical regulator of endothelial necroptosis and metastasis. Human and murine endothelial cells lacking TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…TAK1 deletion resulted in increased expression of RIPK3 in endothelial cells and enhanced both necroptosis of endothelial cells and metastasis of tumor cells (Yang et al, 2019). Deficiency of RIPK3 effectively inhibited tumor metastasis in epithelium-specific TAK1 knockout mice (Yang et al, 2019). These results support the idea that sustained TAK1 signaling is required for controlling the low levels of necroptosis components in endothelial cells.…”
Section: Necroptosis In the Promotion Of Metastasissupporting
confidence: 54%
See 1 more Smart Citation
“…TAK1 deletion resulted in increased expression of RIPK3 in endothelial cells and enhanced both necroptosis of endothelial cells and metastasis of tumor cells (Yang et al, 2019). Deficiency of RIPK3 effectively inhibited tumor metastasis in epithelium-specific TAK1 knockout mice (Yang et al, 2019). These results support the idea that sustained TAK1 signaling is required for controlling the low levels of necroptosis components in endothelial cells.…”
Section: Necroptosis In the Promotion Of Metastasissupporting
confidence: 54%
“…Recently, it has been reported that endothelial TGF-β-activated kinase 1 (TAK1) acts as a negative regulator of endothelial necroptosis and metastasis (Yang et al, 2019). TAK1 deletion resulted in increased expression of RIPK3 in endothelial cells and enhanced both necroptosis of endothelial cells and metastasis of tumor cells (Yang et al, 2019). Deficiency of RIPK3 effectively inhibited tumor metastasis in epithelium-specific TAK1 knockout mice (Yang et al, 2019).…”
Section: Necroptosis In the Promotion Of Metastasismentioning
confidence: 99%
“…These distinctions get further complicated if necroptosis is positioned within a tumor tissue context. For example, IL1α release from necroptotic cancer cells can stimulate the "bystander" stromal cells to proliferate thereby auto-fueling tumor progression via stroma-derived growth factors [20,217,220,251]. Similarly, necroptosis-associated release of reactive nitrogen intermediates (RNI) and/or ROS, at threshold levels, may facilitate pro-tumorigenic processes [20].…”
Section: Necroptosis-driven Modulation Of Anticancer Immunitymentioning
confidence: 99%
“…Together, these results suggested that intravitreal injection of 5Z-7-oxozeaenol does not result in adverse or toxic effects on retinal function and structure up to 28 days post-injection. DISCUSSION TAK1 is a key modulator involved in a range of cellular functions including the immune response (14), cell survival and death (16), angiogenesis (20), fibrosis (30) and tumor metastasis (31). TAK1 is activated in response to various stimuli such as pro-inflammatory cytokines, hypoxia, oxidative stress, metabolism, DNA damage, Wnt and osmotic shock (14,(32)(33)(34).…”
Section: Inhibition Of Tak1 Attenuates Retinal Neovascularization In mentioning
confidence: 99%